2020
DOI: 10.3390/jpm10040232
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 37/67kDa Laminin-1 Receptor Restores APP Maturation and Reduces Amyloid-β in Human Skin Fibroblasts from Familial Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a fatal neurodegenerative disorder caused by protein misfolding and aggregation, affecting brain function and causing dementia. Amyloid beta (Aβ), a peptide deriving from amyloid precursor protein (APP) cleavage by-and γ-secretases, is considered a pathological hallmark of AD. Our previous study, together with several lines of evidence, identified a strict link between APP, Aβ and 37/67kDa laminin receptor (LR), finding the possibility to regulate intracellular APP localization and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Tan & Gleeson, 2019). Accordingly, we and others have demonstrated that intracellular trafficking is extremely important for the correct protein function and processing (Bhattacharya, Izzo, et al, 2020;Sarnataro et al, 2017;J. Z.…”
Section: Endocytosis β -Amyloidogenesis and Pathogenesis Of Admentioning
confidence: 97%
See 1 more Smart Citation
“…Tan & Gleeson, 2019). Accordingly, we and others have demonstrated that intracellular trafficking is extremely important for the correct protein function and processing (Bhattacharya, Izzo, et al, 2020;Sarnataro et al, 2017;J. Z.…”
Section: Endocytosis β -Amyloidogenesis and Pathogenesis Of Admentioning
confidence: 97%
“…The use of receptor inhibitors revealed the possibility to modulate APP maturation and intracellular localization in neuronal cells, as well as to restore the lost “correct” APP intracellular localization, mitochondrial network and Aβ levels in fibroblasts from familial AD‐affected patients (Bhattacharya, Izzo, et al, 2020 ; Bhattacharya, Limone, et al, 2020 ).…”
Section: The Role Of 37/67 Kda Laminin‐1 Receptor (Rpsa) In the Inter...mentioning
confidence: 99%
“…Furthermore, the well-known involvement of O-GlcNAcylation in controlling protein localization, function, and interaction has acquired special interest with regards to APP. Indeed, this posttranslational modification (PTM) has been demonstrated to control APP maturation and trafficking, thus affecting the generation Aβ [ 32 , 33 , 34 ]. Moreover, mitochondrial dysfunction and the associated oxidative stress have been recognized as important biological mechanisms contributing to insulin resistance and diabetic complications [ 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Primary skin fibroblasts isolated from punch biopsies of SSc and healthy skin were mechanically dissociated under a light microscope and trypsinizated, as previously described [ 31 , 48 ]. Cells were plated and cultured in monolayer in DMEM (Life Technologies) supplemented with 10% heat inactivated FBS (Life Technologies), 100 U/mL penicillin G sodium and 100 mg/mL streptomycin sulfate, at 37 °C, in a humidified atmosphere of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%